THE EFFECT OF LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE AGAINST EMPLOYEE JOB PERFORMANCE OF STATE UNIVERSITY OF MEDAN’S LIBRARY UNIT - lit mulina sembiring (Jurnal Pustaka Nusantara dan Budaya, 2013)
The research was conducted in State University of Medan’s Library. The purpose of this study was to determine: 1) the influence of leadership style on employee job performance of UNIMED’s library, 2) the influence of organizational culture on employee job performance of UNIMED’s library and 3) the influence of leadership styles and organizational cultures together towards employee job performance of UNIMED’s library. This research is expected to be useful: 1) as an input for the UNIMED’s library in determining policies to improve employee performance of UNIMED’s library, 2) as a reference material for further research, 3) as the contribution for empirical scholars about how to improve employee job performance by knowing the leadership style and organizational cultureof  UNIMED’s library. Population and at the same sample in this study were employees of State University of Medan’s Library, amounting to 40 people. Data was collected through observation, study literature and questionnaires. Measurement of research variables through a questionnaire using Likert scale. Interpretation of the data is done by a large percentage of the respondents answer. To test the hypothesis used regression and correlation analysis using statistical software SPSS version 17.00. The conclusion is: 1) there is a positive and significant relationship leadership style on employee job performance of UNIMED’s Library, 2) there is a positive and significant relationship of organizational culture on employee job performance UNIMED’s Library, 3) there is a positive and significant relationship of leadership style and organizational culture together to employee job performance of UNIMED’s library, 4) variable overall leadership style and organizational culture influence of 55.8% on job performance, while 44.2% is influenced by other variables that are not addressed in this study